Single-Step Formation of Ni Nanoparticle-Modified Graphene–Diamond Hybrid Electrodes for Electrochemical Glucose Detection - Naiyuan Cui; Pei Guo; Qilong Yuan; Chen Ye; Mingyang Yang; Minghui Yang; Kuan W. A. Chee; Fei Wang; Li Fu; Qiuping Wei; Cheng-Te Lin; Jingyao Gao (Sensors, 2019)
The development of accurate, reliable devices for glucose detection has drawn much attention from the scientific community over the past few years. Here, we report a single-step method to fabricate Ni nanoparticle-modified graphene−diamond hybrid electrodes via a catalytic thermal treatment, by which the graphene layers are directly grown on the diamond surface using Ni thin film as a catalyst, meanwhile, Ni nanoparticles are formed in situ on the graphene surface due to dewetting behavior. The good interface between the Ni nanoparticles and the graphene guarantees efficient charge transfer during electrochemical detection. The fabricated electrodes exhibit good glucose sensing performance with a low detection limit of 2 μM and a linear detection range between 2 μM−1 mM. In addition, this sensor shows great selectivity, suggesting potential applications for sensitive and accurate monitoring of glucose in human blood.